(untitled) (Research, Society and Development, 2021)
The purpose was to verify the association between sociodemographic and health characteristics with the perception of healthy eating among Brazilian participating in the international study Eat-Mot. The perception of healthy eating was investigated by frequency categorized into: never/rarely/sometimes and most of the times/always. Ordinal logistic regression was used to calculate “odds ratio” to verify the relationship between sociodemographic and health variables with the perception of healthy eating. Six hundred and sixty individuals participated, most of them women (74,7%) who have completed higher education or ongoing (77,6%). A good number of the interviewees perceived their diet as healthy (49,3%). In multivariate analysis, it was noted that there was a negative association between the perception of healthy eating with: be male (OR=0,45; IC95%: 0,31-0,64); have less education (high school: OR=0,51; IC95%: 0,35-0,74 and elementary school: OR=0,11; IC95%: 0,03-0,42); less practice of physical activity (>3 times/week: OR=0,40; IC95%: 0,25-0,63, 2-3 times/week: OR=0,29; IC95%: 0,16-0,52; <once/week: OR=0,24; IC95%: 0,14-0,41; and never: OR=0,13; IC95%: 0,08-0,22) and higher body mass index (OR=0,94; IC95%: 0,91-0,97). The results showed the relevance of studies of this nature to encourage the adoption of multiple healthy behaviors, with special attention to the less educated male group.